2016
DOI: 10.11118/actaun201563062187
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Factors Influencing Flights Delay at Czech International Airports

Abstract: ZÁMKOVÁ MARTINA, PROKOP MARTIN. 2015. The Evaluation of Factors Infl uencing Flights Delay at Czech International Airports. Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 63(6): 2187-2196.The main goal of this article was examination of factors infl uencing fl ights delay at three most important international airports in Czech Republic. Data of selected Airlines operating in Czech Republic, whose fl ights are mainly oriented to international airports in Prague, Brno and Ostrava, were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Our survey shows that delayed previous flights of individual planes are precisely the most common cause of delays; they comprise of about 90 % of all delayed flights. As Zámková, Prokop (2015a) and Zámková, Prokop (2016) suggested in their research, the delay caused by the delay of the preceding flight occurs generally very often. Even though the findings in this case apply specifically to European airports, Zámková, Prokop (2016) have also revealed that the delays caused by the delays of preceding flights at airports situated in popular Czech tourists' destinations occur the least frequently at night.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our survey shows that delayed previous flights of individual planes are precisely the most common cause of delays; they comprise of about 90 % of all delayed flights. As Zámková, Prokop (2015a) and Zámková, Prokop (2016) suggested in their research, the delay caused by the delay of the preceding flight occurs generally very often. Even though the findings in this case apply specifically to European airports, Zámková, Prokop (2016) have also revealed that the delays caused by the delays of preceding flights at airports situated in popular Czech tourists' destinations occur the least frequently at night.…”
Section: Resultsmentioning
confidence: 99%
“…As Zámková, Prokop (2015a) and Zámková, Prokop (2016) suggested in their research, the delay caused by the delay of the preceding flight occurs generally very often. Even though the findings in this case apply specifically to European airports, Zámková, Prokop (2016) have also revealed that the delays caused by the delays of preceding flights at airports situated in popular Czech tourists' destinations occur the least frequently at night. While an article by Skorupski, Wierzbinska (2015) deals with the problems arising from waiting for belated passengers, our analysis shows that late passenger does not represent an important issue at Czech airports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review shows up that all most all similar size and activity airports, the main delay factors are weather, technical problems, and reactionary delay. In Zamkova's paper [ 14 ] the main goal was an examination of factors influencing flight delay at three most important international airports in the Czech Republic (Praha, Brno, Ostrava). 5777 flights are investigated in the overall period.…”
Section: Related Workmentioning
confidence: 99%
“…A delayed flight may propagate delays to the next flight through shared resources, such as aircraft, crew, and passengers [23]. This, in turn, may also lead to new delays to other flights through shared airport resources during the ground phase [24]. Baspinar and Koyuncu [25] have successfully applied the SIS model into an air transportation network to study the spreading of flight delay.…”
Section: Flight-based Susceptible-infected-susceptible Modelmentioning
confidence: 99%